The relationship between the Hervormde Kerk in Suidelike Afrika and the Nederduitsch Hervormde Kerk van Afrika in the new South Afrika: co-existence or merger? 1 - Manala, Matsobane J. (Hervormde teologiese studies, 2000)
The article points out that the debate on churck unity cannot be confuted to either a spiritual or structural perspective. It is argued that the church, both risible and invisible, is a given reality. Racially based beliefs are identified as the cause of the separate existence of the NHKA and the HKSA. It is indicated that the true and tenable foundation for the church's mission work and ecclesiastical organisation is the love of God, which makes possible true Christian fellowship, service and witness. Ater pointing to developments in the enpnatien between the two churches, on which structural unity can be built, the aticle makes a strong call for a merger of the two churches in the new South Afica for the sake of positive witness to Christ's mission in the world.